Estimating Successful Internal Mobility: A Comparison Between Structural Equation Models and Machine Learning Algorithms - Bossi, Francesco; Di Gruttola, Francesco; Mastrogiorgio, Antonio; D'Arcangelo, Sonia; Lattanzi, Nicola; Malizia, Andrea P.; Ricciardi, Emiliano (Frontiers in Artificial Intelligence, 2022)
Internal mobility often depends on predicting future job satisfaction, for such employees subject to internal mobility programs. In this study, we compared the predictive power of different classes of models, i.e., i) traditional Structural Equation Modelling (SEM), with two families of Machine Learning algorithms: ii) regressors, specifically least absolute shrinkage and selection operator (Lasso) for feature selection and iii) classifiers, specifically Bagging meta-model with the k-nearest neighbors algorithm (k-NN) as a base estimator. Our aim is to investigate which method better predicts job satisfaction for 348 employees (with operational duties) and 35 supervisors in the training set, and 79 employees in the test set, all subject to internal mobility programs in a large Italian banking group. Results showed average predictive power for SEM and Bagging k-NN (accuracy between 61% and 66%; F1 scores between .51 and .73). Both SEM and Lasso algorithms highlighted the predictive power of resistance to change and orientation to relation in all models, together with other personality and motivation variables in different models. Theoretical implications are discussed for using these variables in predicting successful job relocation in internal mobility programs. Moreover, these results showed how crucial it is to compare methods coming from different research traditions in predictive Human Resources analytics.